2007
DOI: 10.1375/bech.24.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Obsessive Compulsive Symptoms: Similarities and Contrasts with Symptoms of Depression in a Turkish Sample

Abstract: Contemporary cognitive theories of obsessive-compulsive disorder (OCD) propose that certain types of dysfunctional beliefs and assumptions play a salient role in the genesis and persistence of OCD (e.g., Clark, 2004; Rachman, 1993, 1997; Salkovskis, 1985). The present study aimed to examine whether the three proposed dysfunctional beliefs — inflated sense of responsibility, thought suppression, and thought-action fusion — play a significant role particularly on the persistence of obsessive–compulsive (OC) symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Not surprisingly, the intrusion and suppression results reflected the full scale results. These findings provide further support for the notion that the WBSI is best conceptualized as measuring a unitary construct of thought suppression (Altin & Gencoz, 2007; Palm & Strong, 2007; Wegner & Zanakos, 1994)…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Not surprisingly, the intrusion and suppression results reflected the full scale results. These findings provide further support for the notion that the WBSI is best conceptualized as measuring a unitary construct of thought suppression (Altin & Gencoz, 2007; Palm & Strong, 2007; Wegner & Zanakos, 1994)…”
Section: Discussionsupporting
confidence: 70%
“…The paradoxical increase in these thoughts could then result in increased distress, greater attention toward the feared sensations and ultimately panic attack symptomatology (see Figure 3). OCD has been associated with AS (Olatunji & Wolitzky-Taylor, 2009) as well as the use of thought suppression to deal with intrusive thoughts (Altin & Gencoz, 2007; Smári & Hólmsteinsson, 2001). It has been postulated that intrusive thoughts may be particularly distressing for individuals with OCD because of their tendency to overvalue both the consequences and significance of these thoughts (Rassin, et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The original version of this scale incorporates five items that examine the occurrence of intrusive thoughts; several research groups suggest excluding these items to more directly assess suppression per se (Muris, Merckelbach, & Horselenberg, 1996;Rassin, 2003), which was adapted during the present study. The Turkish version of the WBSI has satisfactory reliability and validity in both clinical and nonclinical samples (Altın & Gençö z, 2007;Yorulmaz, Karancı, Baş tug, Kısa, & Gö ka, 2007).…”
Section: White Bear Suppression Inventory (Wbsi; Wegner and Zanakos 1994)mentioning
confidence: 99%
“…In addition, cognitive theories posit that negative appraisals of intrusive thoughts—based on maladaptive beliefs related to responsibility, overestimation of threat, and intolerance of ambiguity, among others—are fundamental to the development and maintenance of OCD symptoms (OCCWG, 1997, 2005; Rachman, 1976; Salkovskis, 1985). These beliefs demonstrate relative specificity to OCD and predict change in OCD symptoms over time (Abramowitz, Nelson, Rygwall, & Khandker, 2007; Altin & Gençöz, 2007; Coles & Horng, 2006; Tolin, Woods, & Abramowitz, 2003; Wu & Carter, 2008). In sum, research has identified distinct OCD symptom dimensions, which are linked through shared etiological mechanisms and symptom function.…”
Section: Introductionmentioning
confidence: 98%